"Análisis económico de la producción del cultivo de sacha INCHI (Plukenetia volubilis linneo) en el Recinto El Vergel del Cantón Valencia". - Herrera Jácome, Darío Fernando (2014)
This thesis entitled "Economic Analysis of Crop Production Sacha Inchi (Plukenetia volubilis Linnaeus) in the Canton Campus El Vergel Valencia" has seven chapters. The first chapter provides the contextual framework of the research topics were taken into account; introduction, objectives and hypotheses. Sacha Inchi , ecology for the production of Sacha Inchi , production system , economic analysis , costs, expenses , income, status , issues having to do with the investigation, relating to definitions and concepts as described in the theoretical framework income, profitability, cost benefit, marketing, marketing channels, market, price, demand, supply, product and factors of production relationship. The third chapter refers to the methods, types, design, research sources and techniques that were applied in the development of this thesis, information processing and analysis of results................................................... .